The melanin-concentrating hormone system as a target for the treatment of sleep disorders - Potter, Liam E.; Burgess, Christian R. (Frontiers in Neuroscience, 2022)
Given the widespread prevalence of sleep disorders and their impacts on health, it is critical that researchers continue to identify and evaluate novel avenues of treatment. Recently the melanin-concentrating hormone (MCH) system has attracted commercial and scientific interest as a potential target of pharmacotherapy for sleep disorders. This interest emerges from basic scientific research demonstrating a role for MCH in regulating sleep, and particularly REM sleep. In addition to this role in sleep regulation, the MCH system and the MCH receptor 1 (MCHR1) have been implicated in a wide variety of other physiological functions and behaviors, including feeding/metabolism, reward, anxiety, depression, and learning. The basic research literature on sleep and the MCH system, and the history of MCH drug development, provide cause for both skepticism and cautious optimism about the prospects of MCH-targeting drugs in sleep disorders. Extensive efforts have focused on developing MCHR1 antagonists for use in obesity; however, few of these drugs have advanced to clinical trials, and none have gained regulatory approval. Additional basic research will be needed to fully characterize the MCH system’s role in sleep regulation, for example, to fully differentiate between MCH-neuron and peptide/receptor-mediated functions. Additionally, a number of issues relating to drug design will continue to pose a practical challenge for novel pharmacotherapies targeting the MCH system.